Gray areas : how the way we work perpetuates racism and what we can do to fix it - Wingfield, Adia Harvey, 1977- (Amistad, an imprint of HarperCollinsPublishers, 2023)
A leading sociologist looks at why racial inequality still exists in the workplace despite the multi-billion-dollar diversity industry's efforts to fight it and offers solutions for reversing the trend to create a truly equitable future.